2010
DOI: 10.1371/journal.pone.0014100
|View full text |Cite
|
Sign up to set email alerts
|

The Biphasic Increase of PIP2 in the Fertilized Eggs of Starfish: New Roles in Actin Polymerization and Ca2+ Signaling

Abstract: BackgroundFertilization of echinoderm eggs is accompanied by dynamic changes of the actin cytoskeleton and by a drastic increase of cytosolic Ca2+. Since the plasma membrane-enriched phospholipid phosphatidylinositol 4,5-bisphosphate (PIP2) serves as the precursor of inositol 1,4,5 trisphosphate (InsP3) and also regulates actin-binding proteins, PIP2 might be involved in these two processes.Methodology/Principal FindingsIn this report, we have studied the roles of PIP2 at fertilization of starfish eggs by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 68 publications
4
45
1
Order By: Relevance
“…As aforementioned, nearly all experimental paradigms that rearranged cortical actin networks resulted in alteration of either amplitude or spatiotemporal dynamics of Ca 2+ signals. Interestingly, when the structure of the cortical actin was modified, the starfish eggs were prone to polyspermy as was observed with heparin, jasplakinolide, and sequestration of PIP2 [105,106]. These eggs also failed to undergo a normal elevation of the fertilization envelope although they were contacted by multiple sperm and produced comparable level of Ca 2+ signals at fertilization.…”
Section: Calcium and Actin At Fertilizationmentioning
confidence: 90%
See 3 more Smart Citations
“…As aforementioned, nearly all experimental paradigms that rearranged cortical actin networks resulted in alteration of either amplitude or spatiotemporal dynamics of Ca 2+ signals. Interestingly, when the structure of the cortical actin was modified, the starfish eggs were prone to polyspermy as was observed with heparin, jasplakinolide, and sequestration of PIP2 [105,106]. These eggs also failed to undergo a normal elevation of the fertilization envelope although they were contacted by multiple sperm and produced comparable level of Ca 2+ signals at fertilization.…”
Section: Calcium and Actin At Fertilizationmentioning
confidence: 90%
“…However, direct measurements of cGMP, cADPr and InsP 3 at fertilization have shown that the increase in the level of cGMP is followed by those of cADPr and InsP 3 , and the major rise of InsP 3 takes place only after the Ca 2+ wave has already initiated [110]. Likewise, in the experiment where the real time changes of the PIP2 levels at the plasma membrane were monitored in a living cell by the use of the RFP-fused marker that contained the PH domain of PLC-δ1 RFP, the starfish eggs at fertilization displayed the initial Ca 2+ rise nearly 10 sec before the plasma membrane PIP2 level began to decline as a result of PLC activation [106]. Hence, these results cast a doubt on the role of InsP 3 as the very first triggering message of Ca 2+ signaling at fertilization.…”
Section: Calcium and Actin At Fertilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…During the ''slow'' block the extracellular ''vitelline'' layer surrounding the oocyte is lifted and converted into a fertilization envelope. In starfish (echinoderm), lifting of the VL has been shown to depend on actin remodeling beginning at the site of sperm entry (Chun and Santella, 2009;Chun et al, 2010;Kyozuka et al, 2008;Puppo et al, 2008).…”
Section: Polyspermy Barriermentioning
confidence: 99%